Pengembangan LKPD Berbentuk Majalah Berbasis Berpikir Kritis Pada Tema 8 Subtema 4 Kelas II SDN 13 Pontianak Timur - Suci Gustyananda; Hery Kresnadi; Rio Pranata (Journal on Education, 2023)
This research aims to develop learner worksheets that are in accordance with the characteristics of students in critical thinking reasoning in thematic learning. This research aims to determine the feasibility of the product. The method used is Research and Development (R&D) and refers to the Borg and Gall development model according to Sugiyono by taking 4 stages, namely (1) Potential and Problems, (2) Data Collection, (3) Product Design, and (4) Design Validation. The data obtained is mixed data, namely quantitative and qualitative data obtained from material content experts, design experts, language experts, and practitioners. The instrument used in the research used was a questionnaire. The level of validity based on material content experts obtained an overall percentage of 86% with a very feasible category, design experts obtained a percentage of 90% with a very feasible category, and language experts obtained a percentage of 90% with a very feasible category. Thus, based on the results of the validated assessment, the development product developed in this study is categorized as very feasible to use in learning.